Promoting sustainable practices in tourist hotels: Examining environment-oriented humble leadership and its green consequences - Farrukh Durrani; Syed Haider Khalil; Muhammad Tufail (Sustainable Futures)
Considering the emphasis on eco-friendly behaviours, we investigated the role of environment-oriented humble leadership (EOHL) and its association with the employees’ green constructive voice (GCV) and green self-efficacy (GSE) using the green organizational identity (GOI) and resource commitment as a key boundary condition. Our hypotheses, based on social learning and social identity theories, were tested with multi-wave, multisource survey data. Data were collected from 465 employees and 465 supervisors working in the tourist hotels of Pakistan. Results confirm the positive association of EOHL with GCV and GSE via the mediation of GOI and moderation of resource commitment. Our findings advance the understanding of organisational environmental management, such as promoting green outcomes by highlighting the critical role of EOHL, GOI, and organizational resource commitment, which is crucial for sustained and effective performance.